Economic Evaluation Methodologies of Remote Patient Monitoring for Chronic Conditions: Scoping Review - Siri Bjorvig; Elin Breivik; Jordi Piera-Jiménez; Carme Carrion (Journal of Medical Internet Research)
Abstract BackgroundRemote patient monitoring (RPM) offers a potential solution to manage the increasing prevalence of chronic condition challenges in health care systems worldwide, but its economic evaluation remains challenging. ObjectiveThis scoping review aimed to explore the methodologies used in economic evaluations of RPM interventions for chronic conditions, with a particular focus on cost identification, measurement and valuation, and reporting quality. MethodsA scoping review was conducted following the Joanna Briggs Institute methodology for scoping reviews. Systematic searches were carried out in Embase, MEDLINE, CINAHL, and Web of Science in week 40 of 2023, with no restrictions on the start date. No geographical restrictions were applied beyond requiring English-language publications. Studies were included if they reported a full or partial economic evaluation of an RPM intervention targeting patients with one or more chronic conditions. Screening and selection were performed independently by 2 reviewers. A total of 5473 records were identified, of which, 41 records met inclusion criteria after screening. Data were synthesized into key themes: study characteristics (design, population, setting), economic evaluation methods (types of analysis, comparator, perspectives, and outcome measures), cost estimation (identification, measurement, valuation), and adherence to the CHEERS (Consolidated Health Economic Evaluation Reporting Standards) 2022. Discrepancies were resolved through discussion. The review protocol was registered in the Open Science Framework. ResultsA total of 41 papers, representing 40 studies, were included in the final review. Studies used diverse evaluation methods, such as cost-effectiveness analysis (20 studies), within which, 13 studies specifically conducted cost-utility analysis. Other approaches included cost-consequence analysis (7 studies), cost-minimization analysis (3 studies), cost-benefit analysis (2 studies), cost analysis (8 studies), and budget impact analysis (1 study). Cost estimation approaches varied across studies, with differences in cost identification, measurement, and valuation. Cost estimation methodologies varied, both in terms of which cost components were included and how costs were identified, measured, and valued. Commonly reported costs related to health care resource use and technology, but the data sources used, and the level of transparency provided, varied. Studies reported a range of outcome measures, including quality-adjusted life years, mortality, and financial indicators. Some studies reported multiple outcomes. Reporting inconsistencies were observed, and adherence to updated CHEERS 2022 standards was limited, particularly in sensitivity analyses and cost data transparency. ConclusionsThis review highlights the diversity and methodological variability in economic evaluations of RPM interventions for chronic conditions. Key limitations include inconsistent cost methodologies and inadequate adherence to reporting standards, complicating cross-study comparisons. Future research should adopt more standardized, transparent reporting protocols to improve the reliability and utility of economic evidence for decision-makers considering RPM implementation.